DETERMINAN MINAT NASABAH DALAM MEMILIH PEMBIAYAAN SYARIAH - Hertika, Elvira; Saiful, Saiful; Suranta, Eddy (UNIB Press, 2016)
The purpose of this research is to determine the influence of knowledge, religious obligation, attitude, social influence and pricing of islamic personal financing toward the intention to use islamic personal financing. This research was conducted on PT Bank BNI Syariah Branch of Bengkulu.The populations of this research were customers who use of Islamic personal financing at PT Bank BNI Syariah Branch of Bengkulu both existing customers or new customers. The data are collected from the questionnaire filled by 89 customers who use the of Islamic personal financing. The data analysis method of this research was processing by SmartPLS.The results show that knowledge an social influence have the positive significant influence toward the intention the customer in choosing the Islamic personal financing. Pricing of islamic personal financing have positive influence while religious obligation, attitude has no influence toward the intention the customer in choosing the Islamic personal financing. The results of this study have implications for more effective strategies can be recommended to attract bank customers to use Islamic personal financing. The findings of this study should be of value to Islamic banks in terms of expanding their customer base.